Cross-Border Transport Corridors: Assessing the Influence of Policy, Technology, and Sustainability Practices on Regional Development, East Africa - Flory , Okandju Okonge; Nyaronga, George (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2025)
This study evaluated the influence of policy frameworks, technology adoption, and sustainability practices on regional development within cross-border transport corridors, focusing on the Central Corridor in East Africa. A mixed-method approach was employed, incorporating both quantitative surveys and qualitative interviews with logistics companies operating within the corridor. The quantitative analysis, using descriptive and regression techniques, demonstrates that effective policies and technological advancements significantly contribute to enhancing operational efficiency and promoting regional development. However, sustainability practices, while gaining attention, face implementation challenges. The study highlights the need for integrated policy approaches that balance technological innovation and sustainability for long-term development.